Career progression among women : a case study in Sabah hospitality industry - Pinky, Thomas (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study aims to identify the factors that contributed towards women employees' career progression in Sabah's hospitality industry. The hotels involved were Cititel Express, Kinabalu Daya Hotel and Imperial International Hotel. One of the objectives of this research was to identify the level of women's career progression in Sabah's hotels whether it is low, moderate or high. There were five hypotheses generated which are to examine the relationship between organizational climate, network access, gender stereotypes, family support, work family balance and women 's career progression. This study also aimed to identify the most dominant factor that contributed towards women's career progression in Sabah's hotels. The data were collected using questionnaires in which the questions had been adapted from previous researches. Pilot study was carried out in two Sabah's hotels which are The Palace Hotel and Shangri-La's Tanjung Aru Beach Resort & Spa before the actual study was conducted. The data were analyzed using Pearson Correlation Analysis and Multiple Regressions Analysis. The findings of this research indicated that organizational climate, network access, family support and work family balance were the factors that had contributed towards women's career progression in Sabah 's hotels. However, gender stereotypes did not have a significant relationship with women's career progression in Sabah's hotels. Meanwhile, the result of the Multiple Regression Analysis showed that organizational climate was the most dominant factor that had contributed towards women's career progression in Sabah's hotels. Few recommendations had been made especially to the Human Resource Practitioners in order for them to ensure that women employees have equal opportunities like men in terms of career progression in the hotels. In addition, few recommendations had been made for future research.